Detection of Inclusion Body Hepatitis in Broiler Chickens in Syria (Journal of Hama University, 2023)
In recent years, Clinical cases of Inclusion Body Hepatitis (IBH) in chickens had increased worldwide due to several sero-types of Avian Adenoviruses that are member of Adenoviridae family. This caused huge economic losses in many countries such as the United States, India, Canada, Hungary, Korea, Lebanon and Spain.Over the past few years, similar cases have been reported in broiler herds in the Syrian Arab Republic. Therefore, we have conducted this study object after an appropriate research plan was designed. Samples from 10 broiler flocks (25-40 days of age) were collected from the Syrian coast region and the countryside of Homs. The samples were taken from birds that showed general symptoms such as lethargy, huddling, ruffled feathers, and inappetence, signs of anemia in legs, skin and bare areas of feathers, and yellow, mucoid droppings. Post-mortem examination showed that the liver is often swollen and enlarged and has yellowish discoloration and multiple pale and/or red (haemorrhagic) foci, enlargement of kidneys and hydropericardium was observed in some birds.Samples of the affected liver were taken from those infected birds and preserved in 10% formalin to detect any Inclusion bodies histologically.  Twenty-six samples showed INIBs from the total of 100 samples and 5 samples were suspected to the presence of INIBs.All samples were stored in a -80° C deep freezer for a molecular biological study.By performing PCR. 11 samples were positive for the presence of FADs from a total of 15 samples.This study is the first to detect the presence of avian adenoviruses in poultry flocks in Syria.
Keywords: Broiler Chickens - Inclusion Body Hepatitis-Fowl Adenovirus - Polymerase chain reaction.